Textbook Analysis for Enhancing Arabic Listening and Writing Skills - Said, Said Al Zaiim Bani; Hikmah, Khizanatul (Indonesian Journal of Islamic Studies, 2024)
This study rigorously examines the content of maharah istima' wal kitabah (listening and writing skills) within the textbook "Al-Lughatu Al-Arabiyyah," using the criteria established by Abdurrahman bin Ibrahim Al-Fauzan. The research holds significant implications for the effective development of Arabic language proficiency. Employing a qualitative content analysis approach, the study meticulously scrutinizes the learning materials, exercises, and assessments pertinent to maharah istima' wal kitabah. Through content analysis techniques, the study unveils that "Al-Lughatu Al-Arabiyyah" adequately satisfies the 'good' category, achieving a commendable 70% for maharah istima' and a 'sufficient' category with a 60% rating for maharah kitabah. These findings offer valuable insights for educators and textbook authors in crafting materials that optimize students' listening and writing skills development. Highlight: Comprehensive Assessment: The study employs a meticulous content analysis approach, evaluating various aspects including learning materials, exercises, and assessments, to provide a comprehensive understanding of maharah istima' wal kitabah proficiency. Abdurrahman Al-Fauzan's Criteria: The research utilizes the established criteria by Abdurrahman bin Ibrahim Al-Fauzan, ensuring a rigorous and standardized assessment of the textbook's material content. Pedagogical Recommendations: The study's findings offer practical recommendations for educators and textbook authors, guiding the development of materials that effectively enhance students' listening and writing skills in Arabic. Keyword: Arabic Language Proficiency, Textbook Analysis, Listening Skills, Writing Skills, Content Evaluation